2006
DOI: 10.2193/0022-541x(2006)70[61:wrfwit]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Waste Rice for Waterfowl in the Mississippi Alluvial Valley

Abstract: Flooded rice fields are important foraging habitats for waterfowl in the lower Mississippi Alluvial Valley (MAV). Waste rice previously was abundant in late autumn (140–492 kg/ha), but early planting and harvest dates in recent years may have increased losses of waste rice during autumn before waterfowl arrive. Research in Mississippi rice fields revealed waste‐rice abundance decreased 79–99% during autumns 1995–1996 (Manley et al. 2004). To determine if this trend existed throughout the MAV, we used multistag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
117
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(124 citation statements)
references
References 16 publications
6
117
1
Order By: Relevance
“…For example, in Mississippi in 1995, Manley et al (2004 documented a mean decrease in waste rice of 79% from 492 kg/ha in August-September to <60 kg/ha in early December. Similarly, Stafford et al (2006) reported that waste rice abundance in Arkansas, Louisiana, Mississippi and Missouri, declined an average of 71% from 271 kg/ha after harvest in early autumn to 78 kg/ha in early winter during [2000][2001][2002]. Because experimental evidence suggests that waterfowl cease foraging and depart rice fields when seed abundance decreases to a "giving-up" density of ~50 kg/ha (Reinecke et al 1989;Greer et al 2009), waste rice apparently contributes less to winter carrying capacity of waterfowl in the MAV than previously thought (Loesch et al 1994;Stafford et al 2006).…”
Section: Rice Seedsmentioning
confidence: 98%
See 3 more Smart Citations
“…For example, in Mississippi in 1995, Manley et al (2004 documented a mean decrease in waste rice of 79% from 492 kg/ha in August-September to <60 kg/ha in early December. Similarly, Stafford et al (2006) reported that waste rice abundance in Arkansas, Louisiana, Mississippi and Missouri, declined an average of 71% from 271 kg/ha after harvest in early autumn to 78 kg/ha in early winter during [2000][2001][2002]. Because experimental evidence suggests that waterfowl cease foraging and depart rice fields when seed abundance decreases to a "giving-up" density of ~50 kg/ha (Reinecke et al 1989;Greer et al 2009), waste rice apparently contributes less to winter carrying capacity of waterfowl in the MAV than previously thought (Loesch et al 1994;Stafford et al 2006).…”
Section: Rice Seedsmentioning
confidence: 98%
“…The majority of this food is in the form of grain spilled or not collected during harvest and commonly referred to as "waste rice" (Stafford et al 2006). Additionally, many birds forage on recently-planted rice seeds, seedlings and grains maturing in seed heads before harvest.…”
Section: Rice Seedsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, economic losses due to blackbird depredations on rice in USA are estimated at US $ 21 million annually (Cummings et al, 2005). After harvest, waste rice remaining in the fields can be a significant source of food for waterfowl (Manley et al, 2004;Stafford et al, 2006). Post-harvest birds in agricultural fields can be beneficial in some situations by gleaning crop seeds not removed by mechanical harvesting and thus reducing the potential for volunteers in a subsequent growing season.…”
Section: Introductionmentioning
confidence: 99%